Capital Punishment in the Lens of the Shari’ah - Abdulrazaq Kilani (IJUS | International Journal of Umranic Studies, 2022)
Shari’ah as a legal system of law in Islam is greatly misunderstood by a cross section of the intellectuals due to the prescription of capital punishments in the legal system. The paper provides explanation for capital punishment in the Shari’ah using the absolute sources of Islam (Qur’an and Sunnah) and to explain that the Shari’ah and Islamic system provide for reform, forgiveness and pardon. The paper concludes that the revulsion against the Shari’ah and its prescriptions is misplaced as Islamic system is replete with prescriptions of mercy and pardon for offenders.